Pelatihan Manajemen Kelas Anti–Bullying dalam Meningkatkan Efektivitas Pembelajaran Bagi Guru dan Tenaga Pendidik di SD Negeri Pasar Lama 6 Banjarmasin - Farial Farial; Jarkawi Jarkawi; Angga Taufan Dayu (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program aimed to enhance the understanding and skills of teachers and educational staff in implementing anti-bullying classroom management to create a safe and effective learning environment at SD Negeri Pasar Lama 6 Banjarmasin. The training consisted of four stages—preparation, implementation, application, and evaluation—and applied a participatory approach through interactive lectures, case studies, group discussions, and role-play simulations. The evaluation showed significant improvement in participants’ competencies, with the average score increasing from 59.78 (pre-test) to 87.17 (post-test), a gain of 27.39 points. Participants’ satisfaction also reached an average score of 4.78, categorized as excellent. These results demonstrate that the Anti-Bullying Classroom Management Training effectively improved teachers’ ability to prevent and handle bullying cases, while also enhancing classroom learning effectiveness and promoting a positive and collaborative school climate.